Electrochemical method for rapidly detecting uric acid and application thereof

By using a micro-pump on a microfluidic chip to control the mixing ratio and flow rate, combined with the magnetic separation and modified electrode catalytic layer of Fe3O4@PDA-PB, the problems of repeatability and specificity in the electrochemical detection of uric acid were solved, achieving rapid and accurate uric acid detection while reducing costs.

CN121476327APending Publication Date: 2026-02-06杭州泰熙生物技术有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511499115.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-20
Publication Date
2026-02-06

AI Technical Summary

Technical Problem

Existing microfluidic chip-based electrochemical detection methods for uric acid suffer from problems such as difficulty in accurately controlling sample dilution and reagent mixing, poor repeatability of detection results, and insufficient detection specificity. In particular, interfering substances in the sample are difficult to separate effectively, affecting the accuracy of the detection results.

Method used

A micro-injection pump is used to control the mixing ratio and injection flow rate of the diluted sample and Fe3O4@PDA-PB suspension. The Fe3O4@PDA-PB specifically binds uric acid in the magnetic separation zone and adsorbs it onto the channel wall through a magnetic field. Combined with differential pulse voltammetry scanning and the catalytic layer of the modified electrode, uric acid oxidation is accelerated, enabling rapid detection of uric acid.

Benefits of technology

It improves the repeatability and specificity of detection, reduces detection costs, enables rapid and accurate detection of uric acid, and the microfluidic chip can be reused 5-8 times, improving detection efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention provides an electrochemical method for rapidly detecting uric acid and application thereof, and the electrochemical method comprises the following steps: S1, mixing a diluted sample with a Fe3O4 (at) PDA-PB suspension according to a volume ratio of (8-10): 1 by using a microinjection pump to form a mixed sample, and injecting the mixed sample into a pretreated microfluidic chip sample injection area at a flow rate of 5-10 [mu] L / min; s2, enabling the mixed sample obtained in the step S1 to flow through a magnetic separation area, specifically combining Fe3O4 (at) PDA-PB with uric acid in the sample, and adsorbing the Fe3O4 (at) PDA-PB on a channel wall under the action of a magnetic field to realize separation from interferents; s3, enabling the sample purified in S2 to flow into a detection area fixed with a modified electrode, standing for 1-1.5 min, starting differential pulse voltammetry scanning, accelerating uric acid oxidation through a catalyst layer of a working electrode, and recording uric acid oxidation peak current; and S4, after detection, enabling the solution to flow into a waste liquid area, and flushing the micro-fluidic chip with a phosphate buffer solution for three times. The method can effectively meet the requirement for uric acid detection in clinical or batch scenes, and is particularly suitable for early warning of subclinical hyperuricemia.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of uric acid detection technology, specifically to a rapid electrochemical method for detecting uric acid and its application. Background Technology

[0002] Uric acid, as the end product of purine metabolism in the human body, is closely related to diseases such as gout, hyperuricemia, and kidney damage due to abnormal concentrations in blood or urine. Therefore, rapid and accurate detection of uric acid is of great significance for clinical diagnosis and disease monitoring. Currently, uric acid detection methods mainly include biochemical enzymatic methods, high-performance liquid chromatography (HPLC), and electrochemical detection methods. Among them, electrochemical detection methods have broad application prospects in the field of point-of-care testing due to their advantages of simple operation, rapid response, and low cost. In recent years, the combination of microfluidic technology and electrochemical detection has enabled the integration of micro-sample analysis and detection processes, further promoting the miniaturization of uric acid detection technology.

[0003] While existing microfluidic chip-based electrochemical detection solutions for uric acid have improved sample volume and detection efficiency, they still have significant technical limitations. On the one hand, sample dilution and reagent mixing often rely on manual operation or simple injection structures, making it difficult to accurately control the mixing ratio and injection flow rate. This can easily lead to poor repeatability of test results due to operational errors, failing to meet the stability requirements of clinical testing. On the other hand, interfering substances such as proteins and ascorbic acid in the sample are difficult to separate effectively. These substances compete with uric acid for electrode reaction sites, interfering with the accurate identification of uric acid oxidation signals, resulting in insufficient detection specificity and affecting the accuracy of the results. Summary of the Invention

[0004] To address the problems existing in the prior art, this invention provides a rapid electrochemical method for detecting uric acid and its application.

[0005] To achieve the above objectives, the present invention provides the following technical solution: This application discloses a rapid electrochemical method for detecting uric acid, the steps of which are as follows: S1. The diluted sample and Fe3O4@PDA-PB suspension are mixed at a volume ratio of 8-10:1 using a micro-injection pump to form a mixed sample, which is then injected into the pretreated microfluidic chip injection area at a flow rate of 5-10 μL / min. S2. The mixed sample obtained in S1 is passed through the magnetic separation zone. Fe3O4@PDA-PB specifically binds to uric acid in the sample and is adsorbed onto the channel wall under the action of the magnetic field, thus achieving separation from the interfering substances. S3. The sample purified by S2 is flowed into the detection area with the modified electrode fixed, and left to stand for 1-1.5 min. The differential pulse voltammetry scan is started to accelerate the oxidation of uric acid through the catalytic layer of the working electrode and the peak current of uric acid oxidation is recorded. S4. After detection, the solution flows into the waste liquid area and the microfluidic chip is rinsed with phosphate buffer 3-5 times. The rinsed microfluidic chip can be reused 5-8 times.

[0006] By setting up the above technical solution, the mixing ratio (volume ratio 10:1) of the diluted sample and the injection flow rate (5-10 μL / min) of the polydopamine-Prussian blue coated Fe3O4 (Fe3O4@PDA-PB) suspension can be precisely controlled by a micro-injection pump, which can reduce manual operation errors and improve detection repeatability. The specific binding of uric acid in the magnetic separation zone by the polydopamine-Prussian blue coated Fe3O4 (Fe3O4@PDA-PB) and its adsorption onto the channel wall by a magnetic field can effectively separate interfering substances in the sample, enhancing detection specificity. After the purified sample is allowed to stand in the detection zone, differential pulse voltammetry scanning, combined with the accelerating effect of the modified electrode catalyst layer on uric acid oxidation, can quickly obtain a clear uric acid oxidation peak current, achieving rapid uric acid detection. After detection, the microfluidic chip can be rinsed with phosphate buffer 3-5 times and reused 5-8 times, reducing detection costs and further improving the practical efficiency of the method.

[0007] The preferred method for preparing the Fe3O4@PDA-PB suspension is as follows: 1) Under nitrogen protection, dissolve 0.6-0.9g FeCl3·6H2O and 0.25-0.35g FeCl2·4H2O in 25-35mL of deionized water, stir at 450-650r / min, and add 6-9mL of 25% ammonia water dropwise over 8-10min. Heat to 62-72℃ and react for 35-50min to obtain Fe3O4 particles. Collect the particles by centrifugation at 8500r / min for 11-13min, and then wash with deionized water 3-4 times. 2) Disperse the Fe3O4 particles obtained in step 1) in 35-45 mL Tris-HCl buffer, add 0.15-0.25 g dopamine hydrochloride, stir at 350-550 r / min at room temperature for 1.2-2.2 h to form Fe3O4@PDA, collect by centrifugation at 8500 r / min for 11-13 min, and then wash with deionized water 2-3 times; 3) Disperse Fe3O4@PDA in 25-35 mL of deionized water, add 0.06-0.12 g of Prussian blue powder, and place it in an ultrasonic disperser with a power of 350-450 W for ultrasonic dispersion for 25-35 min. Then stir the reaction at 350-550 r / min for 1.2-1.8 h, centrifuge at 8500 r / min for 11-13 min to collect the product, wash it three times alternately with deionized water and anhydrous ethanol, and then dry it under vacuum at 55-65℃ for 7-9 h to obtain Fe3O4@PDA-PB powder. Mix the powder with deionized water at a mass ratio of 0.006:1-0.012:1, place it in an ultrasonic disperser with a power of 350-450 W for ultrasonic dispersion for 20-25 min to obtain Fe3O4@PDA-PB suspension.

[0008] By implementing the above technical solution, the preparation of Fe3O4 particles under nitrogen protection can avoid Fe... 2+ Oxidation ensures magnetic purity, and repeated centrifugation and washing remove unreacted raw materials and impurities, providing a pure core for subsequent coating. Dopamine hydrochloride in Tris-HCl buffer reacts with Fe3O4 particles to form Fe3O4@PDA, which can introduce amino and hydroxyl groups, laying the foundation for subsequent specific binding of uric acid. Prussian blue powder is ultrasonically dispersed (350-450W) and then reacted with Fe3O4@PDA to achieve uniform coating of Prussian blue and improve dispersibility. Vacuum drying (55-65℃) ensures that the Fe3O4@PDA-PB powder is dry and pure. Finally, the suspension obtained by ultrasonic dispersion after mixing with deionized water in proportion has good uniformity and no obvious agglomeration. In this suspension, the magnetic properties of the Fe3O4 core are compatible with the magnetic separation requirements of microfluidic chips in electrochemical methods for rapid uric acid detection. The polydopamine layer facilitates the specific binding of uric acid, while Prussian blue helps remove interfering substances. Overall, this provides a reliable material basis for magnetic targeting and anti-interference, as well as improving the specificity and accuracy of detection in the method. At the same time, the uniform suspension can also be adapted to the flow of microfluidic channels, avoiding channel blockage.

[0009] Preferably, in step 2), the concentration of the Tris-HCl buffer is 0.1 mol / L and the pH is 8.2-8.6.

[0010] By setting up the above technical solution, a stable weakly alkaline environment and sufficient buffer capacity can be provided for the reaction of dopamine hydrochloride and Fe3O4 particles: the concentration of 0.1 mol / L can effectively buffer the slight pH fluctuations during the reaction, maintain the stability of the system's acidity and alkalinity, and avoid the reaction process being affected by sudden pH changes; the weakly alkaline conditions of pH 8.2-8.6 are exactly suitable for the self-polymerization requirements of dopamine hydrochloride, which can promote its deprotonation and conversion into dopamine monomers and oxidative polymerization, forming a uniform and complete polydopamine (PDA) layer coated on the surface of Fe3O4 particles. This uniformly coated Fe3O4@PDA can subsequently bind Prussian blue efficiently, and the final polydopamine-Prussian blue coated Fe3O4 (Fe3O4@PDA-PB) can specifically bind uric acid through the amino and hydroxyl groups of the polydopamine layer, laying the foundation for magnetic anti-interference and improving the adsorption specificity of uric acid in the electrochemical method for rapid detection of uric acid, and ensuring the separation efficiency and detection accuracy of interfering substances.

[0011] Preferably, the pretreatment method for the microfluidic chip is as follows: the microfluidic chip is ultrasonically cleaned with deionized water in an ultrasonic cleaner with a power of 200-300W for 5-8 minutes, dried with nitrogen, and then 0.5-1 mg / mL polyethylene glycol solution is injected until the microfluidic chip channel is filled. The chip is allowed to stand at room temperature for 15-20 minutes, and then rinsed three times with phosphate buffer. The concentration of the phosphate buffer is 0.06-0.12 mol / L, the pH is 7.3-7.7, and the number average molecular weight of the polyethylene glycol is 2000.

[0012] By setting up the above technical solution, ultrasonic cleaning with 200-300W deionized water can effectively remove impurities and residues in the channel, ensuring channel cleanliness; after filling the channel with polyethylene glycol (0.5-1mg / mL) with a number average molecular weight of 2000 and allowing it to stand, it can form a hydrophilic coating on the inner wall of the channel, reducing sample adsorption and residue; rinsing three times with phosphate buffer solution at a concentration of 0.06-0.12mol / L and a pH of 7.3-7.7 can not only remove excess polyethylene glycol, but also pre-balance the channel environment (matching the pH of human serum), providing a stable ionic environment for subsequent uric acid detection. Overall, this ensures that the chip channel is clean, adsorb-free, and environmentally compatible, improving detection repeatability and accuracy.

[0013] Preferably, the magnetic separation zone is located between the sample injection zone and the detection zone, and a magnet with a magnetic field strength of 0.15-0.25T is fixed outside it.

[0014] By setting up the above technical solution, when the sample flows through, the polydopamine-Prussian blue coated Fe3O4 (Fe3O4@PDA-PB) is adsorbed onto the channel wall under the action of a magnetic field, specifically binding uric acid and separating interfering substances, preventing interfering substances from entering the detection area, providing a pure sample environment for subsequent electrochemical detection of uric acid, improving detection specificity and accuracy, and meeting the needs of rapid uric acid detection.

[0015] The preferred method for fabricating the modified electrode is as follows: a. Polish the micro glassy carbon electrode to a mirror finish with 0.3μm and 0.05μm Al2O3 polishing powders in sequence, rinse with deionized water, and then place it in an ultrasonic cleaner with a power of 300W for 9-13 minutes for ultrasonic cleaning, and then blow it dry with nitrogen. b. Use a pipette to take 5-7 μL of chitosan-carbon nanotube composite dispersion and uniformly drop it onto the surface of the pretreated micro glassy carbon electrode. Let it air dry at room temperature for 16-22 min to form a conductive fixing layer. c. Use a pipette to take 3-5 μL of NiMn-DAC@CNF dispersion, drop it onto the surface of the conductive immobilization layer, and dry it in a 55-65℃ drying oven for 13-16 min to form a catalyst layer; d. Place the modified electrode 1-1.5 cm above the Fe3O4@PDA-PB suspension and adsorb it for 6-9 min using an external magnet with a magnetic field strength of 0.15-0.25T to form a composite modified electrode of “Fe3O4@PDA-PB / NiMn-DAC@CNF / chitosan-carbon nanotube / micro glassy carbon electrode”.

[0016] By setting up the above technical solutions, the micro glassy carbon electrode can be polished and cleaned to ensure a clean and flat surface, laying the foundation for the firm bonding of subsequent modification layers; the conductive fixing layer formed by the chitosan-carbon nanotube composite dispersion can firmly fix Ni-Mn diatomic doped carbon nanoflowers (NiMn-DAC@CNF) and ensure electron transfer; the catalytic layer formed by Ni-Mn diatomic doped carbon nanoflowers (NiMn-DAC@CNF) can accelerate uric acid oxidation, meeting the needs of rapid detection; the polydopamine-Prussian blue coated Fe3O4 (Fe3O4@PDA-PB) forms an anti-interference layer through magnetic adsorption. The final composite modified electrode has good conductivity, high catalytic activity and anti-interference ability, which can improve the sensitivity, stability and accuracy of uric acid electrochemical detection.

[0017] The preferred method for preparing the NiMn-DAC@CNF dispersion is as follows: (1) Take 1.2-1.8g of citric acid, 2.5-3.5g of urea, 0.3-0.5g of nickel nitrate, and 0.15-0.25g of manganese chloride, add 35-45mL of deionized water, and place it in an ultrasonic disperser with a power of 350-550W for ultrasonic dispersion for 25-35min until the solid is completely dissolved to obtain a transparent mixture; (2) Transfer the transparent mixture to a 50mL polytetrafluoroethylene-lined hydrothermal reactor, seal it, and place it in a forced-air drying oven. React at a constant temperature of 165-185℃ for 6-8 hours to generate carbon nanoflower precursors. (3) After the reaction is complete, cool naturally to room temperature, take out the product, and wash it with deionized water and anhydrous ethanol alternately by centrifugation 4-5 times to remove unreacted raw materials; (4) Transfer the washed solid to a tube furnace and calcine it to 850-920℃ at a heating rate of 6-9℃ / min under a nitrogen atmosphere with a flow rate of 60-120mL / min for 2.5-3.5h. (5) After calcination, the powder is naturally cooled to room temperature, ground through a 250-350 mesh sieve, and mixed with deionized water at a mass ratio of 0.003:1-0.005:1. The powder is then placed in an ultrasonic disperser with a power of 350-550W and ultrasonically dispersed for 30-40 minutes to obtain NiMn-DAC@CNF dispersion.

[0018] By setting up the above technical solution, ultrasonic dissolution achieves uniform mixing of raw materials, hydrothermal reaction generates carbon nanoflower precursors, centrifugal washing removes impurities to ensure purity, calcination in a nitrogen atmosphere reduces metal atom aggregation to form sufficient diatomic catalytic sites, and finally ultrasonic dispersion obtains a uniform dispersion. Its uniformity is conducive to the formation of a consistent catalytic layer in subsequent electrode modification. The diatomic catalytic sites can accurately match the uric acid oxidation potential and improve catalytic efficiency, providing a highly sensitive catalytic basis for the electrochemical method of rapid detection of uric acid, and helping to improve detection sensitivity and signal stability.

[0019] Preferably, the centrifugal washing speed in step (3) is 8500-10500 r / min, and the time for each cycle is 13-16 min.

[0020] By setting up the above technical solution, the carbon nanoflower precursor can be fully precipitated, and unreacted impurities such as citric acid, urea, nickel nitrate, and manganese chloride can be effectively separated and removed, ensuring the purity of the precursor. The pure precursor can be calcined to form uniform Ni-Mn dual-atom doped carbon nanoflowers (NiMn-DAC@CNF) with sufficient active sites, avoiding impurities from interfering with its catalytic performance. This lays the foundation for the efficient acceleration of uric acid oxidation by the catalytic layer in the electrochemical method for rapid detection of uric acid, and helps to improve detection sensitivity and signal stability.

[0021] Preferably, the concentration of the chitosan-carbon nanotube composite dispersion is 1.2-2.2 mg / mL.

[0022] By setting up the above technical solution, a uniform and firm conductive fixation layer can be formed on the surface of the micro glassy carbon electrode: the Ni-Mn dual-atom doped carbon nanoflower (NiMn-DAC@CNF) catalytic layer is firmly fixed by the adhesiveness of chitosan to prevent it from falling off, and the carbon nanotubes ensure good conductivity without hindering electron transfer. This provides a stable electrode substrate for the electrochemical method of rapid detection of uric acid, and helps to improve the stability of the detection signal and the catalytic efficiency.

[0023] This application also discloses a rapid electrochemical method for detecting uric acid, and its application in the detection of uric acid.

[0024] By setting up the above technical solution and realizing automated operation through microfluidic integration, the requirements of rapid detection, high throughput and small error can be met, which can effectively meet the needs of uric acid detection in clinical or batch scenarios, and is especially suitable for early warning of subclinical hyperuricemia.

[0025] The beneficial effects of this invention are as follows: Precise control of the mixing ratio (volume ratio 10:1) and injection flow rate (5-10 μL / min) of the diluted sample and polydopamine-Prussian blue coated Fe3O4 (Fe3O4@PDA-PB) suspension using a micro-injection pump reduces manual operation errors and improves detection repeatability. The specific binding of uric acid in the magnetic separation zone by polydopamine-Prussian blue coated Fe3O4 (Fe3O4@PDA-PB) and its adsorption onto the channel wall via a magnetic field effectively separates interfering substances from the sample, enhancing detection specificity. After the purified sample is allowed to stand in the detection zone, differential pulse voltammetry scanning, combined with the accelerated oxidation of uric acid by the modified electrode catalyst layer, rapidly obtains a clear uric acid oxidation peak current, enabling rapid uric acid detection. The microfluidic chip can be reused 5-8 times after rinsing with phosphate buffer 3-5 times following detection, reducing detection costs and further improving the practical efficiency of the method.

[0026] Preparing Fe3O4 particles under nitrogen protection can avoid Fe 2+Oxidation ensures magnetic purity, and repeated centrifugation and washing remove unreacted raw materials and impurities, providing a pure core for subsequent coating. Dopamine hydrochloride in Tris-HCl buffer reacts with Fe3O4 particles to form Fe3O4@PDA, which can introduce amino and hydroxyl groups, laying the foundation for subsequent specific binding of uric acid. Prussian blue powder is ultrasonically dispersed (350-450W) and then reacted with Fe3O4@PDA to achieve uniform coating of Prussian blue and improve dispersibility. Vacuum drying (55-65℃) ensures that the Fe3O4@PDA-PB powder is dry and pure. Finally, the suspension obtained by ultrasonic dispersion after mixing with deionized water in proportion has good uniformity and no obvious agglomeration. In this suspension, the magnetic properties of the Fe3O4 core are compatible with the magnetic separation requirements of microfluidic chips in electrochemical methods for rapid uric acid detection. The polydopamine layer facilitates the specific binding of uric acid, while Prussian blue helps remove interfering substances. Overall, this provides a reliable material basis for magnetic targeting and anti-interference, as well as improving the specificity and accuracy of detection in the method. At the same time, the uniform suspension can also be adapted to the flow of microfluidic channels, avoiding channel blockage. Detailed Implementation

[0027] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0028] Example 1: This embodiment discloses a rapid electrochemical method for detecting uric acid, the steps of which are as follows: S1. The diluted sample and Fe3O4@PDA-PB suspension were mixed at a volume ratio of 8:1 using a micro-injection pump to form a mixed sample, which was then injected into the pretreated microfluidic chip injection area at a flow rate of 5 μL / min. The diluted sample was obtained by diluting the uric acid sample 10 times with 0.01 mol / L PBS buffer. S2. The mixed sample obtained in S1 is passed through the magnetic separation zone. Fe3O4@PDA-PB specifically binds to uric acid in the sample and is adsorbed onto the channel wall under the action of the magnetic field, thus achieving separation from the interfering substances. S3. The sample purified by S2 is flowed into the detection area with the modified electrode fixed, and left to stand for 1 minute. The differential pulse voltammetry scan is started to accelerate the oxidation of uric acid through the catalytic layer of the working electrode and the peak current of uric acid oxidation is recorded. The magnetic separation zone is located between the sample injection zone and the detection zone, and a magnet with a magnetic field strength of 0.15T is fixed outside it. S4. After detection, the solution flows into the waste liquid area and the microfluidic chip is rinsed 3 times with phosphate buffer. The rinsed microfluidic chip can be reused 5-8 times.

[0029] The preparation method for Fe3O4@PDA-PB suspension is as follows: 1) Under nitrogen protection, 0.6 g FeCl3·6H2O and 0.25 g FeCl2·4H2O were dissolved in 25 mL of deionized water and stirred at 450 r / min. 6 mL of 25% ammonia water was added dropwise at a uniform rate over 8 min. The temperature was raised to 62 °C and the reaction was allowed to proceed for 35 min to obtain Fe3O4 particles. The particles were collected by centrifugation at 8500 r / min for 11 min and then washed three times with deionized water. 2) Disperse the Fe3O4 particles obtained in step 1) in 35 mL Tris-HCl buffer, add 0.15 g dopamine hydrochloride, stir at 350 r / min for 1.2 h at room temperature to form Fe3O4@PDA, collect by centrifugation at 8500 r / min for 11 min, and then wash twice with deionized water. The Tris-HCl buffer solution had a concentration of 0.1 mol / L and a pH of 8.2. 3) Disperse Fe3O4@PDA in 25 mL of deionized water, add 0.06 g of Prussian blue powder, and place it in an ultrasonic disperser with a power of 350 W for 25 min. Then stir the reaction at 350 r / min for 1.2 h, centrifuge at 8500 r / min for 11 min to collect the product, wash it three times alternately with deionized water and anhydrous ethanol, and then dry it under vacuum at 55 °C for 7 h to obtain Fe3O4@PDA-PB powder. Mix the powder with deionized water at a mass ratio of 0.006:1, place it in an ultrasonic disperser with a power of 350 W for 20 min to obtain Fe3O4@PDA-PB suspension.

[0030] The pretreatment method for the microfluidic chip is as follows: the microfluidic chip is ultrasonically cleaned with deionized water in an ultrasonic cleaner with a power of 200W for 5 minutes, dried with nitrogen, and then injected with 0.5 mg / mL polyethylene glycol solution until the microfluidic chip channel is filled. It is then left to stand at room temperature for 15 minutes, and then rinsed 3 times with phosphate buffer. The concentration of phosphate buffer is 0.06 mol / L, the pH is 7.3, and the number average molecular weight of polyethylene glycol is 2000.

[0031] The method for fabricating the modified electrode is as follows: a. The micro glassy carbon electrode was polished to a mirror finish with 0.3μm and 0.05μm Al2O3 polishing powders in sequence, rinsed with deionized water, and then ultrasonically cleaned in an ultrasonic cleaner with a power of 300W for 9 minutes, and dried with nitrogen gas. b. Use a pipette to take 5 μL of chitosan-carbon nanotube composite dispersion with a concentration of 1.2 mg / mL, and uniformly drop it onto the surface of the pretreated micro glassy carbon electrode. Let it air dry at room temperature for 16 min to form a conductive fixing layer. c. Use a pipette to take 3 μL of NiMn-DAC@CNF dispersion, drop it onto the surface of the conductive immobilization layer, and dry it in a 55℃ drying oven for 13 min to form a catalyst layer; d. The modified electrode was placed 1 cm above the Fe3O4@PDA-PB suspension and adsorbed for 6 min by an external magnet with a magnetic field strength of 0.15T to form a composite modified electrode of “Fe3O4@PDA-PB / NiMn-DAC@CNF / chitosan-carbon nanotube / micro glassy carbon electrode”.

[0032] The preparation method of NiMn-DAC@CNF dispersion is as follows: (1) Take 1.2g of citric acid, 2.5g of urea, 0.3g of nickel nitrate and 0.15g of manganese chloride, add 35mL of deionized water, place in an ultrasonic disperser with a power of 350W and ultrasonically disperse for 25min until the solid is completely dissolved to obtain a transparent mixture. (2) Transfer the transparent mixture to a 50 mL polytetrafluoroethylene-lined hydrothermal reactor, seal it, and place it in a forced-air drying oven. React at 165 °C for 6 h to generate carbon nanoflower precursors. (3) After the reaction is complete, the product is naturally cooled to room temperature. The product is then removed and washed 4 times by alternating centrifugation with deionized water and anhydrous ethanol. The centrifugation speed is 8500 r / min and the time is 13 min each time to remove unreacted raw materials. (4) The washed solid was transferred to a tube furnace and calcined at 850°C for 2.5 h under a nitrogen atmosphere with a flow rate of 60 mL / min and a heating rate of 6°C / min. (5) After calcination, the powder was naturally cooled to room temperature, ground through a 250-mesh sieve, mixed with deionized water at a mass ratio of 0.003:1, and ultrasonically dispersed in an ultrasonic disperser with a power of 350W for 30 minutes to obtain NiMn-DAC@CNF dispersion.

[0033] This embodiment also discloses a rapid electrochemical method for detecting uric acid, and its application in uric acid detection.

[0034] Example 2: This embodiment discloses a rapid electrochemical method for detecting uric acid, the steps of which are as follows: S1. The diluted sample and Fe3O4@PDA-PB suspension were mixed at a volume ratio of 10:1 using a micro-injection pump to form a mixed sample, which was then injected into the pretreated microfluidic chip injection area at a flow rate of 10 μL / min. The diluted sample was obtained by diluting the uric acid sample 10 times with 0.01 mol / L PBS buffer. S2. The mixed sample obtained in S1 is passed through the magnetic separation zone. Fe3O4@PDA-PB specifically binds to uric acid in the sample and is adsorbed onto the channel wall under the action of the magnetic field, thus achieving separation from the interfering substances. S3. The sample purified by S2 is flowed into the detection area with the modified electrode fixed, and left to stand for 1.5 min. The differential pulse voltammetry scan is started to accelerate the oxidation of uric acid through the catalytic layer of the working electrode and the peak current of uric acid oxidation is recorded. The magnetic separation zone is located between the sample introduction zone and the detection zone, and a magnet with a magnetic field strength of 0.25T is fixed outside it. S4. After detection, the solution flows into the waste liquid area and the microfluidic chip is rinsed 5 times with phosphate buffer. The rinsed microfluidic chip can be reused 5-8 times.

[0035] The preparation method for Fe3O4@PDA-PB suspension is as follows: 1) Under nitrogen protection, 0.9 g FeCl3·6H2O and 0.35 g FeCl2·4H2O were dissolved in 35 mL of deionized water and stirred at 650 r / min. 9 mL of 25% ammonia water was added dropwise at a uniform rate over 10 min. The temperature was raised to 72 °C and the reaction was allowed to proceed for 50 min to obtain Fe3O4 particles. These particles were collected by centrifugation at 8500 r / min for 13 min and then washed four times with deionized water. 2) Disperse the Fe3O4 particles obtained in step 1) in 45 mL Tris-HCl buffer, add 0.25 g dopamine hydrochloride, stir at 550 r / min for 2.2 h at room temperature to form Fe3O4@PDA, collect by centrifugation at 8500 r / min for 13 min, and then wash 3 times with deionized water. The Tris-HCl buffer solution had a concentration of 0.1 mol / L and a pH of 8.6. 3) Disperse Fe3O4@PDA in 35 mL of deionized water, add 0.12 g of Prussian blue powder, and place it in an ultrasonic disperser with a power of 450 W for 35 min. Then stir the reaction at 550 r / min for 1.8 h, centrifuge at 8500 r / min for 13 min to collect the product, wash it three times alternately with deionized water and anhydrous ethanol, and then dry it under vacuum at 65 °C for 9 h to obtain Fe3O4@PDA-PB powder. Mix the powder with deionized water at a mass ratio of 0.012:1, place it in an ultrasonic disperser with a power of 450 W for 25 min to obtain Fe3O4@PDA-PB suspension.

[0036] The pretreatment method for the microfluidic chip is as follows: the microfluidic chip is ultrasonically cleaned with deionized water in an ultrasonic cleaner with a power of 300W for 8 minutes, dried with nitrogen, and then injected with 1 mg / mL polyethylene glycol solution until the microfluidic chip channel is filled. It is then left to stand at room temperature for 20 minutes, and then rinsed 3 times with phosphate buffer. The concentration of phosphate buffer is 0.12 mol / L, the pH is 7.7, and the number average molecular weight of polyethylene glycol is 2000.

[0037] The method for fabricating the modified electrode is as follows: a. The micro glassy carbon electrode was polished to a mirror finish with 0.3μm and 0.05μm Al2O3 polishing powders, rinsed with deionized water, and then ultrasonically cleaned in an ultrasonic cleaner with a power of 300W for 13 minutes. It was then dried with nitrogen. b. Use a pipette to take 7 μL of chitosan-carbon nanotube composite dispersion with a concentration of 2.2 mg / mL, and uniformly drop it onto the surface of the pretreated micro glassy carbon electrode. Let it air dry at room temperature for 22 min to form a conductive fixing layer. c. Use a pipette to take 5 μL of NiMn-DAC@CNF dispersion, drop it onto the surface of the conductive immobilization layer, and place it in a 65℃ drying oven for 16 min to form a catalyst layer; d. The modified electrode was placed 1.5 cm above the Fe3O4@PDA-PB suspension and adsorbed for 9 min by an external magnet with a magnetic field strength of 0.25T to form a composite modified electrode of “Fe3O4@PDA-PB / NiMn-DAC@CNF / chitosan-carbon nanotube / micro glassy carbon electrode”.

[0038] The preparation method of NiMn-DAC@CNF dispersion is as follows: (1) Take 1.8g of citric acid, 3.5g of urea, 0.5g of nickel nitrate and 0.25g of manganese chloride, add 45mL of deionized water, place in an ultrasonic disperser with a power of 550W and ultrasonically disperse for 35min until the solid is completely dissolved to obtain a transparent mixture. (2) Transfer the transparent mixture to a 50mL polytetrafluoroethylene-lined hydrothermal reactor, seal it, and place it in a forced-air drying oven. React at 185℃ for 8 hours to generate carbon nanoflower precursors. (3) After the reaction is complete, the product is naturally cooled to room temperature. The product is then removed and washed 5 times by alternating centrifugation with deionized water and anhydrous ethanol. The centrifugation speed is 10500 r / min and the time is 16 min each time to remove unreacted raw materials. (4) The washed solid was transferred to a tube furnace and calcined at 920°C for 3.5 h under a nitrogen atmosphere with a flow rate of 120 mL / min and a heating rate of 9°C / min. (5) After calcination, the powder was naturally cooled to room temperature, ground through a 350-mesh sieve, mixed with deionized water at a mass ratio of 0.005:1, and ultrasonically dispersed in an ultrasonic disperser with a power of 550W for 40 minutes to obtain NiMn-DAC@CNF dispersion.

[0039] This embodiment also discloses a rapid electrochemical method for detecting uric acid, and its application in uric acid detection.

[0040] Example 3: This embodiment discloses a rapid electrochemical method for detecting uric acid, the steps of which are as follows: S1. The diluted sample and Fe3O4@PDA-PB suspension were mixed at a volume ratio of 9:1 using a micro-injection pump to form a mixed sample, which was then injected into the pretreated microfluidic chip injection area at a flow rate of 7 μL / min. The diluted sample was obtained by diluting the uric acid sample 10 times with 0.01 mol / L PBS buffer. S2. The mixed sample obtained in S1 is passed through the magnetic separation zone. Fe3O4@PDA-PB specifically binds to uric acid in the sample and is adsorbed onto the channel wall under the action of the magnetic field, thus achieving separation from the interfering substances. S3. The sample purified by S2 is flowed into the detection area with the modified electrode fixed, and left to stand for 1.5 min. The differential pulse voltammetry scan is started to accelerate the oxidation of uric acid through the catalytic layer of the working electrode and the peak current of uric acid oxidation is recorded. The magnetic separation zone is located between the sample introduction zone and the detection zone, and a magnet with a magnetic field strength of 0.2T is fixed outside it. S4. After detection, the solution flows into the waste liquid area and the microfluidic chip is rinsed 4 times with phosphate buffer. The rinsed microfluidic chip can be reused 5-8 times.

[0041] The preparation method for Fe3O4@PDA-PB suspension is as follows: 1) Under nitrogen protection, 0.7g FeCl3·6H2O and 0.3g FeCl2·4H2O were dissolved in 30mL of deionized water and stirred at 550r / min. 7mL of 25% ammonia water was added dropwise at a uniform rate over 9min. The temperature was raised to 67℃ and the reaction was allowed to proceed for 48min to obtain Fe3O4 particles. The particles were collected by centrifugation at 8500r / min for 12min and then washed three times with deionized water. 2) Disperse the Fe3O4 particles obtained in step 1) in 40 mL Tris-HCl buffer, add 0.2 g dopamine hydrochloride, stir at 450 r / min for 1.7 h at room temperature to form Fe3O4@PDA, collect by centrifugation at 8500 r / min for 12 min, and then wash twice with deionized water. The Tris-HCl buffer solution had a concentration of 0.1 mol / L and a pH of 8.4. 3) Disperse Fe3O4@PDA in 30 mL of deionized water, add 0.09 g of Prussian blue powder, and place it in an ultrasonic disperser with a power of 400 W for 30 min. Then stir the reaction at 450 r / min for 1.5 h, centrifuge at 8500 r / min for 12 min to collect the product, wash it three times alternately with deionized water and anhydrous ethanol, and then dry it under vacuum at 60 °C for 8 h to obtain Fe3O4@PDA-PB powder. Mix the powder with deionized water at a mass ratio of 0.009:1, place it in an ultrasonic disperser with a power of 400 W for 22 min to obtain Fe3O4@PDA-PB suspension.

[0042] The pretreatment method for the microfluidic chip is as follows: the microfluidic chip is ultrasonically cleaned with deionized water in an ultrasonic cleaner with a power of 250W for 6 minutes, dried with nitrogen, and then injected with 0.7 mg / mL polyethylene glycol solution until the microfluidic chip channel is filled. It is then left to stand at room temperature for 17 minutes, and then rinsed 3 times with phosphate buffer. The concentration of phosphate buffer is 0.09 mol / L, the pH is 7.5, and the number average molecular weight of polyethylene glycol is 2000.

[0043] The method for fabricating the modified electrode is as follows: a. The micro glassy carbon electrode was polished to a mirror finish with 0.3μm and 0.05μm Al2O3 polishing powders, rinsed with deionized water, and then ultrasonically cleaned in an ultrasonic cleaner with a power of 300W for 11 minutes. It was then dried with nitrogen. b. Use a pipette to take 6 μL of chitosan-carbon nanotube composite dispersion with a concentration of 1.7 mg / mL, and uniformly drop it onto the surface of the pretreated micro glassy carbon electrode. Let it air dry at room temperature for 19 min to form a conductive fixing layer. c. Use a pipette to take 4 μL of NiMn-DAC@CNF dispersion, drop it onto the surface of the conductive immobilization layer, and place it in a 60℃ drying oven for 15 min to form a catalyst layer; d. The modified electrode was placed 1.2 cm above the Fe3O4@PDA-PB suspension and adsorbed for 7 min by an external magnet with a magnetic field strength of 0.2T to form a composite modified electrode of “Fe3O4@PDA-PB / NiMn-DAC@CNF / chitosan-carbon nanotube / micro glassy carbon electrode”.

[0044] The preparation method of NiMn-DAC@CNF dispersion is as follows: (1) Take 1.5g of citric acid, 3g of urea, 0.4g of nickel nitrate and 0.2g of manganese chloride, add 40mL of deionized water, place in an ultrasonic disperser with a power of 450W and ultrasonically disperse for 30min until the solid is completely dissolved to obtain a transparent mixture. (2) Transfer the transparent mixture to a 50mL polytetrafluoroethylene-lined hydrothermal reactor, seal it, and place it in a forced-air drying oven. React at 175℃ for 7 hours to generate carbon nanoflower precursors. (3) After the reaction is complete, the product is naturally cooled to room temperature. The product is then removed and washed 4 times by alternating centrifugation with deionized water and anhydrous ethanol. The centrifugation speed is 9500 r / min and the time is 14 min each time to remove unreacted raw materials. (4) The washed solid was transferred to a tube furnace and calcined at 875°C for 3 hours under a nitrogen atmosphere with a flow rate of 90 mL / min and a heating rate of 7°C / min. (5) After calcination, the powder was naturally cooled to room temperature, ground through a 300-mesh sieve, mixed with deionized water at a mass ratio of 0.004:1, and ultrasonically dispersed in an ultrasonic disperser with a power of 450W for 35 minutes to obtain NiMn-DAC@CNF dispersion.

[0045] This embodiment also discloses a rapid electrochemical method for detecting uric acid, and its application in uric acid detection.

[0046] Comparative Example 1: An electrochemical method for rapid detection of uric acid and its application, which differs from Example 3 only in that NiMn-DAC@CNF was not used in the fabrication of the modified electrode (the composite modified electrode is only Fe3O4@PDA-PB / chitosan-carbon nanotube / micro glassy carbon electrode).

[0047] Comparative Example 2: An electrochemical method for rapid detection of uric acid and its application, which differs from Example 3 only in that the calcination temperature of NiMn-DAC@CNF is changed to 800℃.

[0048] Comparative Example 3: An electrochemical method for rapid detection of uric acid and its application, which differs from Example 3 only in that Fe3O4@PDA-PB is not used (the composite modified electrode is only NiMn-DAC@CNF / chitosan-carbon nanotube / micro glassy carbon electrode).

[0049] Comparative Example 4: An electrochemical method for rapid detection of uric acid and its application, which differs from Example 3 only in that: the chitosan-carbon nanotube composite dispersion is not used (the composite modified electrode is only Fe3O4@PDA-PB / NiMn-DAC@CNF / micro glassy carbon electrode).

[0050] Comparative Example 5: An electrochemical method for rapid detection of uric acid and its application, which differs from Example 3 only in that the microfluidic chip separation region does not have a fixed magnet.

[0051] Comparative Example 6: An electrochemical method for rapid detection of uric acid and its application, which differs from Example 3 only in that the detection method is replaced by cyclic voltammetry.

[0052] Comparative Example 7: An electrochemical method for rapid detection of uric acid and its application, which differs from Example 3 only in that: a microfluidic chip is not used (manual sample introduction + manual magnetic separation is adopted).

[0053] Comparative Example 8: An electrochemical method for rapid detection of uric acid and its application, which differs from Example 3 only in that the working electrode is replaced with a commercially available uric acid oxidase electrode.

[0054] The uric acid levels in the above-described Examples 1-3 and Comparative Examples 1-8 were tested, and the specific tests are as follows: 1. Reference Standards Main standards: YY / T 1523-2017 In Vitro Diagnostic Reagents for Uric Acid Determination (Kit) and GB / T 37866-2019 General Requirements for Performance Evaluation of In Vitro Diagnostic Reagents; Supporting references: Performance Evaluation Specification for Microfluidic Chip Detection System (T / CSBME 035-2022) and Performance Test Method for Electrochemical Sensors (GB / T 30706-2014).

[0055] 2. Detailed inspection procedures (1) Plotting the standard curve 1) Preparation of uric acid standard solution: Prepare uric acid standard solutions with concentrations of 0.05, 0.1, 0.5, 1, 5, 10, 50, 100, 200, and 500 μmol / L using phosphate buffer (pH 7.4); 2) Chip injection detection: Mix uric acid standard solutions of various concentrations with Fe3O4@PDA-PB suspension at a volume ratio of 10:1, inject the mixture into the microfluidic chip at a flow rate of 8μL / min using a micro-injection pump, start differential pulse voltammetry scanning according to the detection parameters of this scheme, and record the peak current corresponding to each concentration. 3) Plot the curve: With "uric acid concentration (μmol / L)" as the abscissa and "peak current (μA)" as the ordinate, use the linear regression method to fit the standard curve and calculate the regression equation (y=kx+b, where k is the slope and b is the intercept).

[0056] (2) Response time test 1) Take a uric acid standard solution with a concentration of 100 μmol / L and mix it with Fe3O4@PDA-PB suspension at a volume ratio of 10:1; 2) Inject the mixture into the microfluidic chip using a micro-injection pump, and record the time from the start of injection until the peak current reaches 90% of the stable value. 3) Repeat the test 6 times and calculate the average of the 6 test results as the final response time.

[0057] (3) Calculation of the limit of detection (LOD) Take blank phosphate buffer (pH 7.4) and perform differential pulse voltammetry scans 12 times consecutively according to the detection parameters of this protocol, and record the peak current of each scan; Calculate the standard deviation (S) of the 12 peak currents, and combine it with the slope (k) of the standard curve to calculate the detection limit according to the formula "LOD=3S / k".

[0058] (4) Anti-interference test 1) Preparation of interference mixture: uric acid concentration 100 μmol / L, ascorbic acid concentration 120 μmol / L, glucose concentration 6 mmol / L, dopamine concentration 60 μmol / L; 2) Mix the interfering mixture with Fe3O4@PDA-PB suspension at a volume ratio of 10:1, and inject it into the microfluidic chip to detect the peak current (denoted as I1). 3) Simultaneously detect the peak current (denoted as I0) of a 100 μmol / L uric acid standard solution free of interfering substances, and calculate the anti-interference rate according to the formula "anti-interference rate (%) = |(I1-I0) / I0|×100%"; 4) Repeat the test 4 times and take the average of the 4 results as the final anti-interference rate.

[0059] (5) Stability test 1) Prepare four identical microfluidic detection chips and store them in a refrigerated environment at 4°C; 2) At storage times of 0d, 7d, 14d, and 21d, take one chip to detect the peak current of 100μmol / L uric acid standard solution, and calculate the retention rate of the peak current at each time point relative to the peak current at 0d. 3) Take one microfluidic chip and continuously test 100μmol / L uric acid standard solution 20 times, and calculate the relative standard deviation (RSD) of the peak current for the 20 tests.

[0060] (6) Spike recovery test 1) Take a commercially available standard serum sample (with a known uric acid concentration of 200 μmol / L), dilute it 10 times with phosphate buffer to obtain a sample stock solution (uric acid concentration of 20 μmol / L). 2) Uric acid standard with concentrations of 50, 100, and 200 μmol / L was added to the sample stock solution to obtain three groups of spiked samples (theoretical concentrations of 25, 30, and 40 μmol / L, respectively). 3) Mix the spiked samples of each group with Fe3O4@PDA-PB suspension at a volume ratio of 10:1, and inject the mixture into a microfluidic chip to detect the actual concentration; 4) Calculate the recovery rate of each spiked sample according to the formula "Recovery rate (%) = (Measured concentration - Sample mother liquor concentration) / Spike amount × 100%". Repeat the test 4 times for each group and take the average value.

[0061] (7) Repeatability test of microfluidic chip 1) Five microfluidic detection chips were fabricated using the same process; 2) Use 5 chips to simultaneously detect 100μmol / L uric acid standard solution and record the peak current of each chip; 3) Calculate the relative standard deviation (RSD) of the peak current of the 5 chips to evaluate the repeatability between chips.

[0062] The results are shown in Table 1.

[0063] Table 1 Performance test results of Examples 1-3 and Comparative Examples 1-8

[0064] Note: Since no microfluidic chip was used, there is no 'inter-chip repeatability' indicator, so the inter-chip RSD is marked as "-".

[0065] Using Example 3 as the control group, the performance differences and causes of Comparative Examples 1-8 are analyzed as follows: Comparative Example 1, which did not use NiMn-DAC@CNF, showed a response time 9 min longer than Example 3 (13 min vs. 4 min), a detection limit increased to 3.5 μmol / L (0.01 μmol / L in Example 3), and an anti-interference rate increased to 9.2% (1.0% in Example 3). This is because the lack of the diatomic catalytic effect of NiMn-DAC@CNF prevented the reduction of the uric acid oxidation energy barrier, significantly slowed electron transfer rates, and eliminated the specific adsorption of uric acid by the catalyst layer, resulting in a substantial decrease in sensitivity and anti-interference ability. This indicates that NiMn-DAC@CNF is the core catalytic component.

[0066] In Comparative Example 2, the calcination temperature of NiMn-DAC@CNF was changed to 800℃ (lower than 875℃ in Example 3), resulting in a 3-minute extension of the response time (7 min vs. 4 min) and an increase in the detection limit to 0.08 μmol / L (0.01 μmol / L in Example 3). Because the calcination temperature was too low, the crystallinity of the carbon nanoflowers was insufficient, and Ni and Mn atoms easily agglomerated, leading to a reduction of approximately 40% in catalytic active sites and a decrease in catalytic efficiency. This demonstrates the rationality of the 875℃ calcination temperature in Example 3.

[0067] Comparative Example 3, which did not use Fe3O4@PDA-PB, showed a significantly higher anti-interference rate of 18.5% compared to Example 3 (1.0%), and a detection limit of 0.12 μmol / L (0.01 μmol / L in Example 3). Due to the lack of magnetic separation from Fe3O4 and the oxidation of interfering substances by Prussian blue, interfering substances such as ascorbic acid and glucose could not be effectively removed, competing with uric acid for catalytic sites, leading to increased peak current fluctuations. This demonstrates that the anti-interference effect of Fe3O4@PDA-PB is indispensable.

[0068] Comparative Example 4, which did not use the chitosan-carbon nanotube composite dispersion, showed a 14-day retention rate of 69.8% (95.2% in Example 3) compared to Example 3, and an RSD of 11.2% after 20 measurements (1.9% in Example 3). Due to the lack of the adhesive fixation of chitosan and the conductive network of carbon nanotubes, NiMn-DAC@CNF easily detached from the electrode surface, and the increased internal resistance of the electrode led to unstable electron transfer, indicating that chitosan-carbon nanotubes play a crucial role in electrode stability.

[0069] In Comparative Example 5, the separation region of the microfluidic chip did not have a fixed magnet, resulting in an anti-interference rate of 19.2% compared to Example 3 (1.0%), and a detection limit of 0.18 μmol / L (0.01 μmol / L in Example 3). Due to the absence of a magnetic field, Fe3O4@PDA-PB could not be adsorbed in the separation region, and interfering substances flowed into the detection region with the sample, leading to increased peak current interference, thus highlighting the necessity of magnetic pretreatment.

[0070] Comparative Example 6 replaced the detection method with cyclic voltammetry, which extended the response time by 12 min compared to Example 3 (16 min vs. 4 min), and increased the detection limit to 0.9 μmol / L (0.01 μmol / L in Example 3). The current resolution of cyclic voltammetry is lower than that of differential pulse voltammetry, and the scan time is longer, making it unable to rapidly capture the uric acid oxidation peak, thus demonstrating the applicability of differential pulse voltammetry for rapid detection.

[0071] Comparative Example 7, which did not use a microfluidic chip, showed a response time 3 minutes longer than Example 3 (7 minutes vs. 4 minutes), and an anti-interference rate of 3.8% (1.0% in Example 3). Manual operation resulted in volumetric errors (±5% vs. ±1% in Example 3), and uneven magnetic field action led to insufficient separation of interfering substances, demonstrating the role of the microfluidic chip in improving detection efficiency and anti-interference capabilities.

[0072] Comparative Example 8 used a commercially available uric acid oxidase electrode, which extended the response time by 15 min compared to Example 3 (19 min vs. 4 min), and increased the detection limit to 7.2 μmol / L (0.01 μmol / L in Example 3). The uric acid oxidase electrode is susceptible to temperature and pH fluctuations, and the enzyme activity decreases with storage time (66.3% retention rate after 14 days vs. 95.2% in Example 3), resulting in significantly lower stability and sensitivity compared to Example 3. This demonstrates the performance advantage of the composite modified electrode (i.e., the working electrode) in this design.

[0073] In summary, precise control of the mixing ratio (volume ratio 10:1) and injection flow rate (5-10 μL / min) of the diluted sample and polydopamine-Prussian blue coated Fe3O4 (Fe3O4@PDA-PB) suspension using a micro-injection pump can reduce manual operation errors and improve detection repeatability. The specific binding of uric acid in the magnetic separation zone by polydopamine-Prussian blue coated Fe3O4 (Fe3O4@PDA-PB) and its adsorption onto the channel wall via a magnetic field effectively separates interfering substances in the sample, enhancing detection specificity. After the purified sample is allowed to stand in the detection zone, differential pulse voltammetry scanning, combined with the accelerating effect of the modified electrode catalytic layer on uric acid oxidation, allows for rapid acquisition of a clear uric acid oxidation peak current, enabling rapid uric acid detection.

[0074] The above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit it. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A rapid electrochemical method for detecting uric acid, characterized in that, The steps are as follows: S1. The diluted sample and Fe3O4@PDA-PB suspension are mixed at a volume ratio of 8-10:1 using a micro-injection pump to form a mixed sample, which is then injected into the pretreated microfluidic chip injection area at a flow rate of 5-10 μL / min. S2. The mixed sample obtained in S1 is passed through the magnetic separation zone. Fe3O4@PDA-PB specifically binds to uric acid in the sample and is adsorbed onto the channel wall under the action of the magnetic field, thus achieving separation from the interfering substances. S3. The sample purified by S2 is flowed into the detection area with the modified electrode fixed, and left to stand for 1-1.5 min. The differential pulse voltammetry scan is started to accelerate the oxidation of uric acid through the catalytic layer of the working electrode and the peak current of uric acid oxidation is recorded. S4. After detection, the solution flows into the waste liquid area and the microfluidic chip is rinsed with phosphate buffer 3-5 times.

2. The rapid electrochemical method for detecting uric acid according to claim 1, characterized in that, The preparation method of the Fe3O4@PDA-PB suspension is as follows: 1) Under nitrogen protection, dissolve 0.6-0.9g FeCl3·6H2O and 0.25-0.35g FeCl2·4H2O in 25-35mL of deionized water, stir at 450-650r / min, and add 6-9mL of 25% ammonia water dropwise over 8-10min. Heat to 62-72℃ and react for 35-50min to obtain Fe3O4 particles. Collect the particles by centrifugation at 8500r / min for 11-13min, and then wash with deionized water 3-4 times. 2) Disperse the Fe3O4 particles obtained in step 1) in 35-45 mL Tris-HCl buffer, add 0.15-0.25 g dopamine hydrochloride, stir at 350-550 r / min at room temperature for 1.2-2.2 h to form Fe3O4@PDA, collect by centrifugation at 8500 r / min for 11-13 min, and then wash with deionized water 2-3 times; 3) Disperse Fe3O4@PDA in 25-35 mL of deionized water, add 0.06-0.12 g of Prussian blue powder, and place it in an ultrasonic disperser with a power of 350-450 W for ultrasonic dispersion for 25-35 min. Then stir the reaction at 350-550 r / min for 1.2-1.8 h, centrifuge at 8500 r / min for 11-13 min to collect the product, wash it three times alternately with deionized water and anhydrous ethanol, and then dry it under vacuum at 55-65℃ for 7-9 h to obtain Fe3O4@PDA-PB powder. Mix the powder with deionized water at a mass ratio of 0.006:1-0.012:1, and place it in an ultrasonic disperser with a power of 350-450 W for ultrasonic dispersion for 20-25 min to obtain Fe3O4@PDA-PB suspension.

3. The rapid electrochemical method for detecting uric acid according to claim 2, characterized in that, In step 2), the concentration of the Tris-HCl buffer is 0.1 mol / L and the pH is 8.2-8.

6.

4. The rapid electrochemical method for detecting uric acid according to claim 1, characterized in that, The pretreatment method for the microfluidic chip is as follows: the microfluidic chip is ultrasonically cleaned with deionized water in an ultrasonic cleaner with a power of 200-300W for 5-8 minutes, dried with nitrogen, and then injected with 0.5-1 mg / mL polyethylene glycol solution until the microfluidic chip channel is filled. The chip is left to stand at room temperature for 15-20 minutes, and then rinsed 3 times with phosphate buffer. The concentration of the phosphate buffer is 0.06-0.12 mol / L, the pH is 7.3-7.7, and the number average molecular weight of the polyethylene glycol is 2000.

5. The rapid electrochemical method for detecting uric acid according to claim 1, characterized in that, The magnetic separation zone is located between the sample injection zone and the detection zone, and a magnet with a magnetic field strength of 0.15-0.25T is fixed outside it.

6. The rapid electrochemical method for detecting uric acid according to claim 1, characterized in that, The method for fabricating the modified electrode is as follows: a. Polish the micro glassy carbon electrode to a mirror finish with 0.3μm and 0.05μm Al2O3 polishing powders in sequence, rinse with deionized water, and then place it in an ultrasonic cleaner with a power of 300W for 9-13 minutes for ultrasonic cleaning, and then blow it dry with nitrogen. b. Use a pipette to take 5-7 μL of chitosan-carbon nanotube composite dispersion and uniformly drop it onto the surface of the pretreated micro glassy carbon electrode. Let it air dry at room temperature for 16-22 min to form a conductive fixing layer. c. Use a pipette to take 3-5 μL of NiMn-DAC@CNF dispersion, drop it onto the surface of the conductive immobilization layer, and dry it in a 55-65℃ drying oven for 13-16 min to form a catalyst layer; d. Place the modified electrode 1-1.5 cm above the Fe3O4@PDA-PB suspension and adsorb it for 6-9 min using an external magnet with a magnetic field strength of 0.15-0.25T to form a composite modified electrode of "Fe3O4@PDA-PB / NiMn-DAC@CNF / Chitosan-carbon nanotube / micro glassy carbon electrode".

7. The rapid electrochemical method for detecting uric acid according to claim 6, characterized in that, The preparation method of the NiMn-DAC@CNF dispersion is as follows: (1) Take 1.2-1.8g of citric acid, 2.5-3.5g of urea, 0.3-0.5g of nickel nitrate, and 0.15-0.25g of manganese chloride, add 35-45mL of deionized water, and place it in an ultrasonic disperser with a power of 350-550W for ultrasonic dispersion for 25-35min until the solid is completely dissolved to obtain a transparent mixture; (2) Transfer the transparent mixture to a 50mL polytetrafluoroethylene-lined hydrothermal reactor, seal it, and place it in a forced-air drying oven. React at a constant temperature of 165-185℃ for 6-8 hours to generate carbon nanoflower precursors. (3) After the reaction is complete, cool naturally to room temperature, take out the product, and wash it with deionized water and anhydrous ethanol alternately by centrifugation 4-5 times to remove unreacted raw materials; (4) Transfer the washed solid to a tube furnace and calcine it to 850-920℃ at a heating rate of 6-9℃ / min under a nitrogen atmosphere with a flow rate of 60-120mL / min for 2.5-3.5h. (5) After calcination, the powder is naturally cooled to room temperature, ground through a 250-350 mesh sieve, and mixed with deionized water at a mass ratio of 0.003:1-0.005:

1. The powder is then placed in an ultrasonic disperser with a power of 350-550W and ultrasonically dispersed for 30-40 minutes to obtain NiMn-DAC@CNF dispersion.

8. The rapid electrochemical method for detecting uric acid according to claim 7, characterized in that, The centrifugal washing in step (3) is performed at a speed of 8500-10500 r / min, and each cycle lasts for 13-16 min.

9. The rapid electrochemical method for detecting uric acid according to claim 6, characterized in that, The concentration of the chitosan-carbon nanotube composite dispersion is 1.2-2.2 mg / mL.

10. The application of the rapid electrochemical method for detecting uric acid according to any one of claims 1-9 in the detection of uric acid.